Design, qualification & manufacture of ITER gravity supports. Issue 3 (March 2020) - Lee, P.Y.; Hou, B.L.; Sun, Z.C.; Kang, D.A.; Han, S.L.; Zhang, T.; Xu, D.; Yan, T.F.; Zhang, B.
Abstract: As one of the key components to support all the magnet coils, the GS faces engineering challenge to its operational safety throughout the design, qualification and manufacturing process as a result of extreme loading condition. The structural safety of GS was confirmed by both the FEM analysis and the semi-prototype engineering test after a long time of design, qualification, manufacture and assembly. Welding the cooling pipe to the flexible plate without obvious deformation as well as tightening uniformly and precisely all the tie rods to clamp the plates were carried out successfully during manufacturing. The result of final vacuum leakage test indicates that the GS can not only meet the ITER vacuum requirement but also have no slow out-gassing. The first set of GS which has passed the ITER acceptance test is to be delivered to ITER construction site soon. Abstract : Energy; Nuclear engineering; Structural engineering; Energy economics; Energy sustainability; Gravity support; Engineering test; FEM analysis; Leakage test